Brand, Consumers, and a Piece of Love: Indonesian Most Engaging Brands 2022 - Achmad Edhy Aruman; Lis Hendriani; Dyah Hasto Palupi; Dwi Wulandari (Jobmark: Journal of Branding and Marketing Communication, 2022)
This article reports and discusses the judging results of The Most Engaging Brands Award 2022 organized by Mix Marketing & Communication. In today's digital era, brand managers are no longer just thinking about brand awareness and image, but also the most important thing is brand engagement. Consumer engagement with the brand occurs because of love; if love is not present, then positive engagement will create love. This premise is evident from several entries in The Most Engaging Brands Award 2022.